Menelaah Dinamika Komunikasi Emosional dan Kebingungan Identitas Melalui Analisis Isi Narasi Lirik 'Mangu' - Nurul Anam, Mohamad; Fakhri K, M; Anwar, Noufan; Alwan, Noufal (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
This study aims to analyze how emotional communication dynamics and identity confusion are constructed within the lyrics of "Mangu", a song by Fourtwnty featuring Charita Utami. Employing a qualitative approach through content analysis, the research explores song lyrics as symbolic texts that represent affective experiences and identity issues within interpersonal relationships. The findings reveal that the lyrics portray emotional expressions such as confusion, inner conflict, and emotional detachment, as well as the articulation of shifting identities driven by differences in values and beliefs. Narrative strategies such as conceptual metaphors, spatial imagery, emotional diction, and implicit narrative progression are utilized to convey these core themes. This study concludes that "Mangu" functions as a complex medium of artistic communication, reflecting psychosocial dynamics in contemporary Indonesian popular culture. The research contributes to the fields of communication studies, popular music analysis, and cultural identity discourse